PENGEMBANGAN MATERI PAI DALAM PENGUATAN BACA TULIS AL-QUR’AN DI SMP PIRI 2 YOGYAKARTA - Mgr Sinomba Rambe; Hendro Widodo (Program Studi Pendidikan Agama Islam Sekolah Tinggi Agama Islam Negeri (STAIN) Teungku Dirundeng Meulaboh Aceh Barat, 2023)
The occurrence of a shift in the era is very influential in the world of education, one of which is the shift in the interests and abilities of students in reading and writing the Qur'an, which is decreasing. Of course, this problem must be immediately addressed and given a solution so that the problem of strengthening Al-Qur'an reading and writing for students can find a solution and complete it. This study aims to analyze the development of PAI materials in strengthening Al-Qur'an reading and writing at SMP Piri 2, Yogyakarta. This research uses a descriptive qualitative research model, namely, researchers who try to understand and interpret an actual event in the field according to the researcher's own point of view, using data collection methods from observations, interviews, and documentation. The results of this study indicate that the strengthening of Al-Qur'an reading and writing at SMP Piri 2 Yogyakarta has been very optimally carried out by educators at the school. Several forms and methods of strengthening Al-Qur'an reading and writing are applied in SMP 2 Piri, including habituation methods, collective tadarus, and memorization. Various methods are used to strengthen the recitation of the Qur'an, including the baghdadiyah method, the qiroati method, the iqra' method, and tahqiq. Tuisa reinforcement also varies greatly, including Imla' manqul, Imla' mandhur, Imla' ikhtiari, and Imla' iktibar, using the sorogan, classical, and reading-seeing systems.